Net-Positive Energy Buildings: Empirical Insights Towards Achieving the SDGs - Mikhail, Monika; Mather, David; Parker, Paul (Journal of Strategic Innovation and Sustainability, 2023)
Buildings impact multiple United Nations (UN) Sustainability Development Goals (SDGs). Net-positive energy buildings (NPEBs) present an opportunity for the built sector to offer climate solutions and habitable environments with improved energy efficiency, responsible consumption, sustainable energy production, and sustainable communities. Case study analysis of a multi-tenant office NPEB demonstrates decisions made to realize the SDGs. Average annual energy consumption of 83 kWh/m2 was one-third that of typical office buildings and the generation of 871 kWh of solar electricity achieved the net-positive goal. This mixed methods performance assessment used four years of energy meter data and key informant interviews to provide a holistic understanding of building energy performance and contributions to the SDGs.